O uso da tecnologia moodle na prática docente em um curso técnico em enfermagem - Cianflone, Luciana Paula de Almeida (2020)
The use of the internet since the 1990s combined with the advancement of multimedia technologies were the instruments to help teachers to qualify the teaching-learning process. The training of nursing technicians for many years has not used information technologies, but currently the process of teaching and the use of platforms can be an ally together with active learning methods. It was intended to identify the possibilities and obstacles to the use of the Moodle platform in a technical nursing course. With qualitative, exploratory and descriptive characteristics, the study counted on the participation of 10 professors that were nurses and through the focus group, statements were collected and organized according to the Collective Subject Discourse, and later themed. Three major thematic categories emerged: the use of the Moodle platform and active learning methods; the institution's infrastructure and the student's commitment to the learning process. There are perspectives for the inclusion of active learning methodologies in the practice of teachers, which can become an innovative pedagogical strategy, but which requires the continuous training of teachers and their motivation. On the other hand, there is a need for the reality and needs of students to be the focus of further research by teachers and educational institutions. New studies are sought in this direction, seeking the innovation and autonomy of these health professionals